Comparative Analysis of Islamic Educational Thought of KH. Hasyim Asy’ari and KH. Ahmad Dahlan - Muhammad Agus Ainur Rasyid; Rohimin Rohimin; Nur Hidayat (FKIP - Universitas Riau, 2026)
This study aims to: (1) examine the educational thought of KH. Hasyim Asy'ari, (2) explore the educational ideas of KH. Ahmad Dahlan, and (3) identify the similarities and differences between the two. This research employs a library research design with a philosophical approach, using literature review as the main data collection technique and descriptive as well as content analysis for data interpretation. The findings reveal that: (1) KH. Hasyim Asy'ari emphasizes Islamic education as a process of forming a complete human being who seeks closeness to Allah SWT and attains happiness in both worldly and spiritual dimensions. (2) KH. Ahmad Dahlan views the purpose of Islamic education as producing individuals who master religious knowledge while possessing a broad and modern worldview. (3) Both scholars share similarities in their educational goals, commitment to Islamic reform, intellectual lineage, emphasis on Islamic education, establishment of educational institutions, efforts to raise Muslim awareness, and focus on building an educated generation, positioning education as a tool for transformation. However, their differences lie in their approaches to religious education, curriculum orientation, teaching methods, and specific educational objectives.